Ludzie w otoczeniu przyrody. O Dwóch księżycach Marii Kuncewiczowej - Szymczak-Maciejczyk, Barbara (Motywy fauny i flory w literaturze i kulturze, 2018)
The charpenter delivers an analysis of a human condition in the collection of stories entitled Two moons. The author considers the issue of the relationship between man and nature. The writer made the division of society into red moon’s people and white moon’s people. The first group is composed of craftsmen, merchants, farmers and beggars. The second group includes the artists and their muses and patrons.Nature is different for each of these communities — the former respects mainly useful plants: fruits, cereals, trees; the second appreciates the fragrant flowers or shrubs. The author presented the above-mentioned division of flora, showed what it depends from and what was the purpose of using this type of perception of the world.